Dielectric Spectroscopy Analyses of SrBi4Ti4O15 Films Obtained from Soft Chemical Solution - Simões, Alexandre Zirpoli [UNESP]; Riccardi, C. S. [UNESP] (Hindawi Publishing Corporation, 2009)
SrBi4Ti4O15 (SBTi) thin films were deposited by the polymeric precursor method on Pt bottom electrodes. The obtained films were characterized by X-ray diffraction, scanning electron microscopy, Raman spectroscopy, and dielectric spectroscopy analyses. The capacitance-voltage (C-V) characteristics of perovskite thin film showed normal ferroelectric behavior. The remanent polarization and coercive fields were 5.4 mu C/cm(2) and 85 kV/cm, respectively. Dielectric spectroscopy was employed to examine the polycrystalline behavior of ferroelectric material and the mechanisms responsible for the dielectric performance of the thin film. Copyright (C) 2009 A. Z. Simoes and C. S. Riccardi.